2014
DOI: 10.1007/s12208-013-0112-x
|View full text |Cite
|
Sign up to set email alerts
|

Social marketing and healthy eating: findings from young people in Greece

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 75 publications
0
12
0
1
Order By: Relevance
“…What is more and more popular is the trend of the so-called healthy eating (Kapetanaki et al 2014;Banna et al 2016;Rafacz 2019). That trend is mostly associated with the consumption of fresh food products, i.e., vegetables and fruit, grown by local farmers, without artificial fertilizers or plant protection chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…What is more and more popular is the trend of the so-called healthy eating (Kapetanaki et al 2014;Banna et al 2016;Rafacz 2019). That trend is mostly associated with the consumption of fresh food products, i.e., vegetables and fruit, grown by local farmers, without artificial fertilizers or plant protection chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory actions from governments and increased efforts from industry and civil society will be necessary to break these vicious cycles (Roberto et al, 2015; Swinburn et al, 2015). Critical social marketers (Gordon, 2011) and those calling for a shift in focus to upstream behavior change propose measures such as restricting the marketing of unhealthy food to children, making healthier food more affordable, for example, through subsidies on fruit and vegetables, and making less healthy food more expensive by using taxes, for example, on sugary drinks (Hawkes et al, 2015; Kapetanaki, Brennan, & Caraher, 2014; Kleinert & Horton, 2015; Wymer, 2010). WHO (2010) published a set of guidelines to help policy makers regulate the marketing of food and drink products to children.…”
Section: Introductionmentioning
confidence: 99%
“…A Greek study highlighted that young students living alone and leading their own household have a more unhealthy diet than those who live together with their parents (Papadakia et al 2007). Kapetanaki and his co-authors (Kapetanaki et al 2014) found that Greek young adults aged 18-24 adopted unhealthier nutritional habits after enrolment. Using a qualitative research method (focus group interviews) the researchers highlighted the motivations for healthy eating-good health, appearance and psychological consequences-and the barriers-lack of time, fast-food availability and taste, peer pressure, lack of knowledge and lack of family support.…”
Section: Theoretical Backgroundmentioning
confidence: 99%